OPTIMAL FISCAL AND MONETARY POLICY, DEBT CRISIS, AND MANAGEMENT. (20th July 2017) - Cantore, Cristiano; Levine, Paul; Melina, Giovanni; Pearlman, Joseph
Abstract : The initial government debt-to-gross domestic product (GDP) ratio and the government's commitment play a pivotal role in determining the welfare-optimal speed of fiscal consolidation in the management of a debt crisis. Under commitment, for low or moderate initial government debt-to-GDP ratios, the optimal consolidation is very slow. A faster pace is optimal when the economy starts from a high level of public debt implying high sovereign risk premia, unless these are suppressed via a bailout by official creditors. Under discretion, the cost of not being able to commit is reflected into a quick consolidation of government debt. Simple monetary–fiscal rules with passive fiscal policy, designed for an environment with "normal shocks, " perform reasonably well in mimicking the Ramsey-optimal response to one-off government debt shocks. When the government can issue also long-term bonds—under commitment—the optimal debt consolidation pace is slower than in the case of short-term bonds only, and entails an increase in the ratio between long- and short-term bonds.